BER Analysis of Underlay Cooperative Cognitive Radio-based NOMA System - Ad, Meriem; Khelil, Abdellatif (International Journal of Sensors Wireless Communications and Control, 2025)
BackgroundThe integration of Cooperative Communications (CC), Cognitive Radio (CR) technology, and Non-Orthogonal Multiple Access (NOMA) techniques, termed Cooperative Cognitive Radio used NOMA (CCR-NOMA) systems, has emerged as a promising solution to address spectrum scarcity and connectivity challenges anticipated in sixth generation (6G) networks.AimsThis study aims to investigate the Bit Error Rate (BER) performance of underlay CCR-NOMA systems.MethodsWe derive precise closed-form expressions for BER at distant users under perfect and imperfect Channel State Information (CSI) conditions. These mathematical formulations are validated through Monte Carlo simulations.Results and DiscussionOur results indicate that the near user 1 exhibits superior performance compared to the far user 2. Additionally, distant users utilizing the CCR-OMA protocol demonstrate better BER performance than those employing the CCR-NOMA protocol.ConclusionThe presence of imperfect CSI adversely affects BER performance. Moreover, the derived closed-form expressions for BER in the investigated system align well with Monte Carlo simulations. These findings provide valuable insights for optimizing the performance of CCR-NOMA systems in real-world scenarios.
Keywords: cooperative communication